Noninvasive prenatal testing detecting metastatic breast cancer: Case report and literature review - Gabriel Francisco Pereira Aleixo; Holly Pederson; Nancy Dalpiaz; Jame Abraham (Current Problems in Cancer: Case Reports, 2024)
Noninvasive prenatal testing (NIPT) analyzes placental cell-free DNA in maternal blood for genetic abnormalities, especially in pregnant women of advanced maternal age. It is a high-sensitivity and specificity test used for screening fetal chromosome trisomy 13, 18, 21, sex chromosome aneuploidy, and rare fetal chromosome aneuploidy. Rarely there were cases in which it was used to diagnose maternal cancer. We will discuss a case of metastatic breast cancer diagnosed by NIPT and current knowledge on the use of this technology in diagnosing cancer during pregnancy.